Cropping and Groundwater Situation in a Canal Command Area - A Case Study - Singh, Bir Pal; Singh, R.P. (Journal of Soil and Water Conservation, 2022)
Water is the most vital input for agricultural production and assured water availability is essential for intensive agriculture. In order to assess the canal water distribution pattern and its influence on the cropping pattern, a study was conducted in Eastern Yamuna Canal command area. A multistage sampling technique was adopted for selecting the study locations, in head, middle and tail reaches of the Canal. The analysis of data collected from the paddy and sorghum- sown areas under the selected distributaries indicate that the farmers are switching over to sorghum from paddy due to uncertainty and inadequacy of canal water. The study also indicates that the water table the ground level has declined from 3 - 4 m during 1970-75 to 24 - 27 m at present due to excessive pumping by well owners.